Decadal time series of tropospheric abundance of N2O isotopomers and isotopologues in the Northern Hemisphere obtained by the long‐term observation at Hateruma Island, Japan. Issue 8 (19th April 2013) - Toyoda, Sake; Kuroki, Natsuko; Yoshida, Naohiro; Ishijima, Kentaro; Tohjima, Yasunori; Machida, Toshinobu
Abstract : [1] Decadal time series and short‐term temporal variations in mixing ratio of atmospheric nitrous oxide (N2 O) and abundance of its isotopomers ( 14 N 15 N 16 O and 15 N 14 N 16 O) and isotopologue ( 14 N 14 N 18 O) relative to 14 N 14 N 16 O have been observed for the first time in the Northern Hemisphere at Hateruma Island (HAT), Japan during 1999–2010 by monthly air sampling. Results show that the bulk nitrogen isotope ratio δ 15 N bulk decreased at the rate of −0.023 ± 0.006‰ yr −1, although the N2 O mixing ratio increased at the rate of about 0.7 nmol mol −1 yr −1 (ppb yr −1 ) during the period. Isotope budget calculation with the δ 15 N bulk trend supports the earlier estimates showing that the isotopically light sources such as agriculture and industry contribute to the increase of atmospheric N2 O. However, the rate of decrease of δ 15 N bulk is slightly smaller in magnitude than the rates obtained virtually for the 20th century from firn air in polar regions and surface air in the Southern Hemisphere (Tasmania and Antarctica), which suggests greater contribution of 15 N‐enriched N2 O sources in recent years or in the extra‐polar Northern Hemisphere. In contrast, the oxygen isotope ratio ( δ 18 O) and intramolecular 15 N site preference ( SP, difference between isotope ratios at central and terminal nitrogen atoms) of N2 O showed no significant trends, contrary to previous reports. Results show that no significant seasonal variation exists in δ 15 N bulk, δ 18 O, and SP of N2 O at HAT in the past decade within the limits of our sampling frequency and analytical precision. Key Points: Mixing ratio and isotope ratios of N2O have been monitored in Japan 15N content of tropospheric N2O decreased during the past 10 years